Sauna finesa. Evidencias de las indicaciones de la sauna. - Balaguer, Francisco Lázaro (Medicina Naturista, 2008)
Finnish and other cultures have used the hot places as sauna for centuries to clean themselves, to maintain their physic, psyche and spirit, their health and even to help in treating a variety of ills; used as a place for childbirth, so as cereals drying place. Finnish sauna is heated by the radiaction energy of an electrical or wood burning stones resulting in high air temperature and low air humidity level. The heat load starts the General Adaptation Mechanism including thermoregulatory mechanism such as the evaporative heat transfer by sweating is the only effective channel dissipating heat from the body. Causes various acute, transient cardiovascular, metabolic and hormonal changes, well tolerated by most healthy adults and childrens, does nor influence fertility and is safe during the uncomplicated pregnancies. Transient improvements in pulmonary function may provide some relief in asthma and chronic bronchitis may alleviate pain and joint mobility in rheumatic disease. Used in detox-programs, to prevent common colds, in Glaucoma, Cerebral Palsy, Chronic Fatigue Syndrome, skin problems, to endurance the performance in sport, in Anorexia and Bulimia nervosa.